Modelling the damage and deformation process in a plastic bonded explosive microstructure under tension using the finite element method - Arora,H; Tarleton,E; Li-Mayer,J; Charalambides,M; Lewis,D (Computational Materials Science, 2015)
Modelling the deformation and failure processes occurring in polymer bonded explosives (PBX)and other energetic materials is of great importance for processing methods and lifetime storagepurposes. Crystal debonding is undesirable since this can lead to contamination and a reductionin mechanical properties. An insensitive high explosive (PBX-1) was the focus of the study.This binary particulate composite consists of (TATB) filler particles encapsulated in a polymericbinder (KELF800). The particle/matrix interface was characterised with a bi-linear cohesive law,the filler was treated as elastic and the matrix as visco-hyperelastic. Material parameters weredetermined experimentally for the binder and the cohesive parameters were obtained previouslyfrom Williamson et al. (2014) and Gee et al. (2007) for the interface. Once calibrated, the materiallaws were implemented in a finite element model to allow the macroscopic response of thecomposite to be simulated. A finite element mesh was generated using a SEM image to identifythe filler particles which are represented as a set of 2D polygons. Simulated microstructureswere also generated with the same size distribution and volume fraction only with the idealisedassumption that the particles are a set of circles in 2D and spheres in 3D. The various modelresults were compared and a number of other variables were examined for their influence on theglobal deformation behaviour such as strain rate, cohesive parameters and contrast between fillerand matrix modulus. The overwhelming outcome is that the geometry of the particles plays acrucial role in determining the onset of failure and the severity of fracture in relation to whetherit is a purely local or global failure. The model was validated against a set of uniaxial tensiletests on PBX-1 and it was found that it predicted the initial modulus and failure stress and strainwell.Keywords: Particulate composites, High volume fraction, Finite Element Analysis,Micromechanics, Fract